The effect of the amount of murabaha financing, mentoring and length of business on increasing income - Puspita, Dara; Imsar, Imsar; Harahap, Muhammad Ikhsan (Goodwood Publishing, 2024)
Purpose: This study aims to examine how Murabahah financing, mentoring programs, and the length of business operation affect the income growth of MSMEs at Bank Sumut KCPSy Multatuli. Methods: The study was conducted at Bank Sumut KCPSy Multatuli and focused on 60 MSME clients. A quantitative approach was used, with data collected through questionnaires. The data analysis was performed using multiple linear regression, processed with SPSS version 25. Results: The research found that the income growth of MSMEs is significantly influenced by Murabahah financing, mentoring programs, and the duration of business operation. These factors together account for 80.7% of the increase in income, while the remaining 20.3% is influenced by other variables not covered in the study. Limitations: The study is limited by its focus on only three factors and its reliance on data from one location, Bank Sumut KCPSy Multatuli, which may not fully capture other variables influencing MSME income growth. Contribution: This study contributes to the understanding of factors driving income growth for MSMEs, particularly in the context of Islamic financing (Murabahah), mentorship, and business longevity. It is useful for policymakers, financial institutions, and researchers in the field of MSME development and Islamic finance. Novelty: The novelty of this research lies in its focus on combining Murabahah financing, mentoring, and business duration as key determinants of income growth for MSMEs in the Indonesian context, which has not been thoroughly explored before.